GluR3B Antibody Was a Biomarker for Drug-Resistant Epilepsy in Patients With Focal to Bilateral Tonic-Clonic Seizures - Lai, Qingwei; Li, Qingyun; Li, Xinyu; Wang, Heng; Zhang, Wei; Song, Xiaotao; Hu, Peng; Yao, Ruiqin; Fan, Hongbin; Xu, Xingshun (Frontiers in Immunology, 2022)
Considering the role of GluR3B antibody-mediated excitotoxicity in the progression of epilepsy, the purpose of this study was to evaluate the clinical significance of GluR3B antibody level as a novel biomarker for the prognosis of unknown etiology drug-resistant epilepsy (DRE) in patients with focal to bilateral tonic-clonic seizures. The study included 193 patients with focal to bilateral tonic-clonic seizures in the modeling cohort. Serum and CSF samples from patients were collected, and GluR3B antibody levels were detected by an ELISA kit. Serum and CSF GluR3B antibody levels in patients with DRE were significantly increased compared with those in patients with drug-responsive epilepsy. Univariate logistic regression analysis underlined that patients with high GluR3B antibody levels had a significantly increased risk of developing DRE. A logistic regression model demonstrated that increased GluR3B antibody levels were an independent factor in predicting DRE. External verification showed that the model constructed for the prediction of DRE had good adaptability. Finally, decision curve analysis highlighted the superior clinical net benefit in DRE prognosis by GluR3B antibody level. In summary, elevated levels of GluR3B antibody are an early biomarker to predict the prognosis of DRE; in addition, targeting GluR3B antibody may be a promising treatment strategy for patients with DRE.